PENGARUH MEKANISME CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP TAX AVOIDANCE - Yudea Yudea (Jurnal Ekonomi Dan Bisnis, 2019)
Tax avoidance is the effort to carried out is legalfor taxpayers. Research aims to examine the effect of corporate governance mechanisms the corporate governance that are firm size and leverage against tax avoidance. The study was conducted on automotive manufacturing companies in the Indonesia Stock Exchange in the period of 2013 - 2017. From a total population of 14, a sample of 6 companies was obtained. Sampling using purposive sampling method. The analysis technique uses multiple linear regression.Results finding is there audit quality have a significant effect on tax avoidance, while the variable proportion of independent commissioners, firm size and leverage does not significantly influence tax avoidance. Keywords: Tax Avoidance, Corporate Governance, Firm Size and Leverage